Effect of an intercalated research degree on general practice careers: a matched cohort study - Ibrahim Saleh Al-Busaidi (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONIntercalated degrees are one of the most focused undergraduate research training activities offered to medical students worldwide. The effect of intercalating on actual career choices has not been previously investigated. AIMTo examine the effect of obtaining an intercalated research degree on choosing general practice as a career. METHODSThis was a retrospective, matched cohort study of intercalating students at the University of Otago, New Zealand (1995-2008). Medical students who completed the intercalated Bachelor of Medical Sciences with Honours, BMedSc(Hons), degree were retrospectively identified. Gender- and graduation year-matched controls were identified from a publicly available graduate database in a 1:1 ratio. MEDLINE® and Google Scholar-indexed publications resulting from BMedSc(Hons) projects were determined using standardised search criteria. Speciality choice was obtained from online lists of registered doctors. RESULTSOver the 14-year period, 99 (3.9%) students completed an intercalated degree with a publication rate of 36.4%. Of these, 42 (42.4%) were female and over two-thirds (68.7%) of projects were laboratory-based. The median follow-up period after graduation was 14 years (range 7.7-21.7 years). The congruence between students' BMedSc(Hons) research subject area and clinical speciality was 9.1%. Sixteen (16.2%) intercalating students chose general practice as a career, whereas 83 (83.8%) chose 19 different hospital-based specialties. Compared to controls, students who completed an intercalated degree were significantly less likely to pursue a career in general practice (odds ratio 0.37; 95% confidence interval=0.18 - 0.77; P=0.007). DISCUSSIONThe present study findings suggest that completing an intercalated degree is associated with lower odds of pursuing a career in general practice. Future research should explore reasons for this observation to help develop strategies to promote primary care and general practice careers among medical graduates, including those interested in research careers.